The impact of malnutrition on efficacy of resistance training in community‐dwelling older adults. (24th October 2018) - Kamo, Tomohiko; Ishii, Hideaki; Suzuki, Keisuke; Nishida, Yuusuke
Abstract: Objective: Few studies have focused on the effect of resistance training under conditions of malnutrition in older adults requiring long‐term care. The purpose of this study was to investigate the influence of nutritional status in older adults on resistance training‐induced changes in physical performance. Methods: A total of 91 community‐dwelling older adults participated in 24 weeks of resistance training. Participants used the 60% of one repetition maximum for three sets of 10 repetitions for resistance training. Short Physical Performance Battery (SPPB), Mini Nutritional Assessment Short Form (MNA‐SF), Barthel Index, and grip strength were measured before and after the resistance training. The participants were classified into three groups according to the MNA‐SF score at baseline (0 to 7 as malnutrition group, 8 to 11 as at risk group, and 12 to 14 as well‐nourished group). Results: In comparing the preintervention and postintervention changes in functional fitness of the groups, there was a significant Group × Time interaction for SPPB scores ( F = 11.59, p < 0.01), 4‐m walk speed ( F = 5.87, p < 0.01), and grip strength ( F = 3.27, p < 0.05). Multivariate logistic regression analysis showed that well‐nourished group was significantly more likely to improvement of physical function (odds ratio 3.08, 95% confidence interval [1.54, 6.15], p < 0.01). Conclusions: The results of study revealed that malnutrition was an independent negative factor of effects of resistance training in older adults. These results suggested that effects of resistance training may be affected by the nutritional state.